MELIHAT BISNIS SEJAK DINI DALAM MENINGKATKAN PRODUKTIVITAS DENGAN MENGGUNAKAN METODE DROPSHIPPING DALAM PERSPEKTIF EKONOMI ISLAM (STUDI PADA MAHASISWA FEBI IAIN BONE) - Nuranna Rahim; Haslindah Haslindah (Institut Agama Islam Negeri Bone, 2021)
This study discusses business from an early age in increasing productivity using the dropshipping method in the perspective of Islamic economics which was carried out among FEBI IAIN Bone students with a qualitative method approach. The results of the study explain that there are several efforts made by FEBI IAIN Bone students in starting their business, namely choosing the business they are engaged in and developing it by introducing to the surrounding environment that the business we run is good, choosing its own advantages in terms of product quality, price, marketing and different product models. Then try to retain customers by maintaining a good name and having a good plan in order to maintain business in the future. Seeing businesses at a young age using themethod dropshipping can increase productivity and this is in accordance with the principles of doing business in Islam. This can be seen from the transparency in entering into cooperation agreements.